Studi Lapangan SSOP (Sanitation Standard Operating Procedure) UKM Kripik Tempe “Mulyo Sari” - Latifasari, Nurul; Dewi, Fitranaya Arlian Cintaya; Awaludin, Muhammad Tata; Wulandari, Devi; Salsa Bilah, Al Haya Nurjanah Afifah; Septiani, Fauziah Bunga; Kurniawan, Rizky (LPPM IT Telkom Purwokerto, 2025)
Small and medium businesses are businesses managed on an individual scale or as an individual business entity. Even though it is small-scale, business actors must still pay attention to hygiene aspects from the start of production until the product reaches the hands of consumers, as stated in Law No. 18 of 2012 concerning Article 70, which states that food sanitation is carried out so that food is safe for consumption. The production of